2019
DOI: 10.1111/os.12444
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Symptomatic Venous Thromboembolism in Patients with Hemophilia Undergoing Hip and Knee Joint Replacement without Chemoprophylaxis: A Retrospective Study

Abstract: Objective To establish the prevalence of clinically significant venous thromboembolic events (VTE) in hemophilia patients undergoing total hip arthroplasty (THA) and total knee arthroplasty (TKA) without chemoprophylaxis and a modified coagulation factor substitution. Methods A cohort of patients who underwent THA and TKA from June 2002 to April 2017 were included. Based on World Federation of Hemophilia (WFH) guidelines, a modified coagulation factor substitution regimen was adopted. All patients were under a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The true incidence of symptomatic venous thromboembolism (VTE) in patients with hemophilia undergoing such surgeries is still uncertain. The estimated incidence in previous retrospective studies ranged from 0% to 1% 10 - 12 , whereas the incidence of symptomatic VTE was as high as 4.3% in 1 prospective multicenter study 13 . In our study, the incidence of VTE was comparable between the hemophilia and control cohorts for both hip (0% versus 0.64%) and knee (1.15% versus 0.98%) procedures.…”
Section: Discussionmentioning
confidence: 90%
“…The true incidence of symptomatic venous thromboembolism (VTE) in patients with hemophilia undergoing such surgeries is still uncertain. The estimated incidence in previous retrospective studies ranged from 0% to 1% 10 - 12 , whereas the incidence of symptomatic VTE was as high as 4.3% in 1 prospective multicenter study 13 . In our study, the incidence of VTE was comparable between the hemophilia and control cohorts for both hip (0% versus 0.64%) and knee (1.15% versus 0.98%) procedures.…”
Section: Discussionmentioning
confidence: 90%
“…The incidence of major bleeding in patients with hemophilia undergoing total hip arthroplasty or total knee arthroplasty in the setting of low-weight molecular heparin use is estimated to be 50% [32]. Moreover, the overall incidence of major bleeding for patients with hemophilia undergoing total joint arthroplasty regardless of prophylaxis type is estimated to be 39.1% [32]. The authors' institution as well as previous reports recommend the use of nonpharmacologic DVT prophylaxis such as IPCDs and early ambulation [10].…”
Section: Discussionmentioning
confidence: 77%
“…Although the use of DVT prophylaxis is of standard protocol in most patients undergoing total joint arthroplasty, the hemophilia population represents a unique cohort in which the risk of bleeding with pharmacologic DVT prophylaxis must be weighed with the risk of venous thromboembolism. The incidence of major bleeding in patients with hemophilia undergoing total hip arthroplasty or total knee arthroplasty in the setting of low-weight molecular heparin use is estimated to be 50% [32]. Moreover, the overall incidence of major bleeding for patients with hemophilia undergoing total joint arthroplasty regardless of prophylaxis type is estimated to be 39.1% [32].…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent study, DVT was not detected by US after TKA in 36 Japanese patients with haemophilia 9 . Retrospective studies from China and the United States have reported that the prevalence of clinically significant VTE among haemophilic patients who underwent TKA and THA without routine chemoprophylaxis was in the range of 0%‐1.4% 15‐17 . These very low rates may underestimate small thrombus formation, because the studies evaluated symptomatic VTE from medical records, not from evaluation of fixed methods 15‐17 .…”
Section: Discussionmentioning
confidence: 97%